Pengaruh Latihan Passing Diamond Terhadap Akurasi Passing Pada Ekstrakurikuler Sepak Bola SMA Negeri 1 Tarik - Achmad Kivlain Zain Pramudyatama; Riga Mardhika (Jurnal Ilmiah Adiraga, 2024)
The study aims to examine passing accuracy on the country high school soccer team 1 attraction. The study employed quantitative research with experimental methods. In this study, one-group research design predesignates the design where it contains pretest and posttest. The sample of this study is an extracurricular student of 20 soccer students. Implement and collection of data in this study USES test methods. Statistical analysis methods used are description analysis, normality tests, homogeneity tests, and t tests using SPSS 22.  Based on the t-test results using version 22, it is noted that the average value (mean) on the pretest and posttest results is -23,000 with significant, rs. 0,000. Research indicates that passing diamond exercises have an impact on extracurricular student soccer 1 interest. Keywords: Passing diamond, accuracy pass, soccer.